Co-variation, style and social meaning: The implicational relationship between (h) and (ing) in Debden, Essex. (October 2020) - Cole, Amanda
Abstract: This paper demonstrates that the differing social meanings held by linguistic features can result in an implicational relationship between them. Rates of (h) and (ing) are investigated in the casual speech of sixty-three speakers from a community with Cockney heritage: Debden, Essex. The indexicalities of h-dropping in Debden (signalling Cockney) are superordinate to and incorporate the indexicalities of g-dropping (working-class, "improper"), resulting in an implicational relationship. H-dropping implies g-dropping, but g-dropping can occur independently of h-dropping. This occurs in terms of co-variation at the between-speaker level and clustering effects at the within-speaker level which is measured through a novel approach using the number of phonemes as the denomination of distance. The features' differing social meaning are also related to rates of change. Young speakers are shifting away from linguistic features which index Cockney heritage (h-dropping; the [-Iŋk] variant of - thing words) in favor of more general, southeastern, working-class norms (g-dropping).